Trend Judi Online dan Pinjol pada Kelompok Remaja : Faktor Resiko dan Dampak Sosial - Ashari, Ibnu Rasyid; Khodijah, Khodijah (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 24 No 2 (2024)DO - 10.24843/PJIIB.2024.v24.i02.p07, 2024)
This article explains the risk factors and social impact of online gambling and online loans that have become a trend among teenagers. Based on the research conducted, there are several interesting things, one of which is that online gambling can be a place to express or create in an instant way without them knowing if this activity has risk factors such as addiction without thinking about the social impact that will occur. This research method uses library research techniques or literature studies that take data from similar research or previous research.